Addition of Tofu Waste to Concentrate Feed on Ruminant Animal Value - Engkus Ainul Yakin; Sri Sukaryani; Catur Suci Purwati; Desi Lestari (Program Studi Peternakan, Fakultas Pertanian, Universitas Veteran Bangun Nusantara, 2019)
The purpose of this study was to determine the effect of the addition of tofu waste in concentrate feed on the nutritional value of ruminant animal feed. Concentrate feed used in this study uses concentrated feed for sheep. Tofu waste was obtained from the place of making tofu in Girimarto sub-district, Wonogiri Regency. The research method used was concentrate feed for sheep given the addition of tofu waste. The study used 3 treatments namely T0 = Concentrate without the addition of tofu waste (control), T1 = Concentrate with 10% tofu waste addition, and T2 = Concentrate with 20% tofu waste addition. The results of the study were analyzed in the laboratory to determine the nutritional value of sheep feed. The study was designed with a completely randomized design. Observation parameters of nutritional value of feed include dry matter, crude protein, crude fiber and in vitro digestibility. The results showed that dry matter content was 78.54 ± 0.23% and crude protein was 16.63 ± 0.46% with the addition of tofu waste until 20% showed a significant difference, whereas crude fiber was 20.37 ± 0.48 % showed no significant difference, while the dry matter digestibility and organic matter digestibility showed no significant difference. The conclusion of this study was the addition of tofu waste in the concentrate had an effect on the dry matter and crude protein, but not significantly different on crude fiber. The addition of tofu waste to the concentrate did not affect the digestibility of dry matter or the digestibility of organic matter.Key words : Animal feed, concentrate, in vitro digestibility, tofu waste